Establishment of a Simple Pediatric Lower Respiratory Tract Infections Database Based on the Structured Electronic Medical Records - Lin, Jilei; Yuan, Shuhua; Dong, Bin; Zhang, Jing; Zhang, Lei; Wu, Jinhong; Chen, Jiande; Tang, Mingyu; Zhang, Bin; Wang, Hansong; Xu, Liangye; Zhao, Liebin; et al. (Frontiers in Pediatrics, 2022)
Objective: This study aimed to establish a pediatric lower respiratory tract infections (PLRTIs) database based on the structured electronic medical records (SEMR), to provide a brief overview and the usage process of the SEMRs and the database. Methods: All the medical information is recorded by a clinical information system developed by EurekaSystems company. A plugin of the software was used to set the properties of items of the SEMR. Children with lower respiratory tract infections (LRTIs) admitted to department of respiratory medicine of our hospital from May, 2020 were included. PostgreSQL 13.1 software was used to construct the PLRTIs database. Results: Seven kinds of SEMR were established, and the admission record was the most important and complex among them. It was mainly composed of 10 parts, including basic information, history of present illness, past history (without respiratory disease), past history of respiratory diseases, personal history, family history, physical examination, the score of LRTIs, auxiliary examination and diagnosis. With the three-level doctor ward round, the recorded information of the SEMR would be checked repeatedly, thus guaranteeing the correctness of the information. The data of the SEMR and laboratory tests could be extracted directly from the hospital information system (HIS) by PostgreSQL 13.1 software with the specific SQL code. After manually checking the original records, the datasets were imported into PostgreSQL 13.1 software, and a simple PLRTIs database was constructed. According to the including criteria of this study, a total of 1184 children with LRTIs were included in this database from May 1st, 2020 to April 30th, 2021. Conclusion: A series of SEMRs for PLRTIs were designed and used during hospitalization. A simple PLRTIs database was established based on the SEMR. The SEMRs will provide complete and high-quality data on LRTIs in children.